How Teacher Performance Moderated by Teacher Competence to Improve Students’ Achievement? - Sherly, Sherly; Lie, Darwin; Dharma, Edy; Sihombing, Humiras Betty Marlina; Sudirman, Acai (FKIP Universitas Lampung, 2022)
Objective The purpose of this study is to analyze teacher performance based on teacher competence which has an impact on student achievement at SMA Negeri 5 Pematangsiantar. Methods: The population in this study amounted to 30 people. The data analysis technique used is quantitative descriptive analysis. Conclusion: The competencies There is a positive influence between teacher competence on teacher performance and there is a positive influence between teacher performance on student achievement. There is a strong and positive relationship between teacher competence and teacher performance and there is a strong and positive relationship between teacher performance and learning achievementpossessed by each teacher will show the real teacher. These competencies are manifested in the form of mastery of knowledge, skills and also professional attitudes in carrying out their functions as teachers. Keywords: teacher performance, teacher competence, student achievement.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.2022333